Acquired and genetic thrombotic risk factors in the athlete - Zadow, E. K.; Adams, M. J.; Kitic, C. M.; Xuan Wu, S. S.; Fell, J. W. (Seminars in Thrombosis & Hemostasis, 2018)
While athletes are often considered the epitome of health due to their physique and lowered potential for metabolic and cardiovascular diseases, they may also be at risk for the onset and development of venous thromboembolism (VTE). In an attempt to achieve and remain competitive, athletes are frequently exposed to numerous athlete-specific risk factors, which may predispose them to VTE through the disruption of factors associated with Virchow's triad (i.e., hypercoagulability, venous stasis, and vessel wall injury). Indeed, hypercoagulability within an athletic population has been well documented to occur due to a combination of multiple factors including exercise, dehydration, and polycythemia. Furthermore, venous stasis within an athletic population may occur as a direct result of prolonged periods of immobilization experienced when undertaking long-distance travels for training and competition, recovery from injury, and overdevelopment of musculature. While all components of Virchow's triad are disrupted, injury to the vessel wall has emerged as the most important factor contributing to thrombosis formation within an athletic population, due to its ability to influence multiple hemostatic mechanisms. Vessel wall injury within an athletic population is often related to repetitive microtrauma to the venous and arterial walls as a direct result of sport-dependent trauma, in addition to high metabolic rates and repetitive blood monitoring. Although disturbances to Virchow's triad may not be detrimental to most individuals, approximately 1 in 1,000 athletes will experience a potentially fatal post-exercise thrombotic incidence. When acquired factors are considered in conjunction with genetic predispositions to hypercoagulability present in some athletes, an overall increased risk for VTE is present.